The Effectiveness of Using E-Court Services in Realizing Electronic Religious Courts - Yusuf Dwi Prasetyo; Dani Muhtada; Martitah Martitah (Eduvest - Journal of Universal Studies, 2025)
The Supreme Court has issued Supreme Court Regulation No. 7 of 2022, which has significant impacts despite generating various societal opinions. It is important to evaluate the implementation of this regulation to ensure the presence and effectiveness of compliance in the electronic court proceedings. The conceptual framework of this research is based on the concepts of e-court services and electronic courts, with the theories employed including policy implementation theory, legal certainty, effectiveness, and legal system theory. The Normative Juridical approach is a legal research method emphasizing the study of norms or legal rules stipulated in legislation. The findings indicate that the implementation of e-court services is outlined in Supreme Court Regulation Number 7 of 2022. Courts must prepare skilled judges and provide adequate infrastructure. The implementation of e-court has successfully increased the efficiency of legal processes and reduced the administrative and financial burden on the parties involved in cases. This research concludes that the implementation of e-court services has brought about increased efficiency in the proceedings of religious civil cases. Recommendations for improvement include conducting evaluations to ensure that all case resolutions through e-court services comply with the letter from the Director General of the Religious Courts Agency dated June 7, 2024, No. 1295/DJA/HK2.6/VI/2024.